Digital HRM with Machine Learning Approach - Muhammad Fauzan Azhmy; Annisha Suvero Suyar; Arasy Ayu Setiamy (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this paper is to provide an overview of how modern resource management resolves conventional challenges in that area. Computing technology with all its specific application variants will help human performance in HR management in the contemporary era. The rapid advancement of technology and digitalization has presented a digital economy characterized by business and the trade transactions based on technology. This study aims to analyze the influence of the digital economy as measured by the Value of Electronic Money Transactions and the Value of E-Commerce Transactions on Indonesia’s economic growth. This research method is descriptive qualitative with a literature study approach. The data sources used are journal manuscripts, books, and other sources that are in accordance with the theme of this study. The data will be elaborated to get the construction of relevant thoughts and reflect an adequate analysis of computers and human resource management in this modern era. The results of the study are computing is able to carry out administrative tasks automatically; computing is able to increase employee engagement; computing can help improve the recruitment and orientation process; computing can help ensure compliance; and computing can help drive data-driven decision making.